Perancangan dan Pembuatan Aplikasi Permainan Edukasi Mathventure Quest Berbasis Android - Trianto, Edwin Meinardi; Ariel Kristianto; Ivan Leonardi Candra; Timothy John Pattiasina; Titasari Rahmawati (Universitas Muhammadiyah Riau, 2024)
Mathematics can be said to be a mandatory subject from elementary school to college or higher education whose function is used to this day. Mathematics lessons are sometimes considered quite difficult subjects by students at school because mathematics is always related to formulas, calculations and numbers. Games are defined as activities that relieve boredom and fill free time. Games can also increase the level of intelligence, increase knowledge and solve problems easily. The author was inspired to create or design an educational game application with a mathematics theme entitled Mathventure Quest using Android-based Unity Engine software. In this game there are enemies that must be fought to move to the next place. The way to fight these enemies is to answer the questions given by the application. If the player can answer, the enemy will lose and move on to the next place. This educational game can help educate and attract the attention of elementary school students with mathematics lessons which can also be a medium of entertainment for elementary school students.